2021
DOI: 10.31849/dinamisia.v5i5.5298
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Pengetahuan tentang Pembangunan Berkelanjutan menggunakan Media Cerita Bergambar ditingkat Sekolah Dasar

Abstract: This community service entitled Enhancement Knowledge of Sustainable Development with Pictorial Story at Elementary School was carried out to strengthen the knowledge capacity and attitude related to groundwater resources in Bronggang Baru, Cangkringan District, Sleman, Yogyakarta. The method of implementing community service was conducted by three steps, consist of 1) literature review and problem analysis, 2) interviews and analysis of partner needs, and 3) developing and delivering the media of pictorial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…From these studies, it is known that worksheets provide many benefits for students, especially in improving critical thinking, students' cognitive learning outcomes, improving students' collaboration skills. Research from Suharman et al, (2021) showed that illustrated story media resulted in students being able to more easily internalize the knowledge and positive values contained in it. Zahroh & Yuliani's (2021) research shows that there is a significant increase in student achievement by using picture story teaching materials.…”
Section: Table 4 Validator Suggestionsmentioning
confidence: 99%
“…From these studies, it is known that worksheets provide many benefits for students, especially in improving critical thinking, students' cognitive learning outcomes, improving students' collaboration skills. Research from Suharman et al, (2021) showed that illustrated story media resulted in students being able to more easily internalize the knowledge and positive values contained in it. Zahroh & Yuliani's (2021) research shows that there is a significant increase in student achievement by using picture story teaching materials.…”
Section: Table 4 Validator Suggestionsmentioning
confidence: 99%
“…Sumber daya air tanah merupakan bagian sains lingkungan. Hasil penelitian terdahulu menguraikan bahwa literasi sains lingkungan lebih mudah dipahami jika divisualkan dalam bentuk media interaktif dan animasi (Dong, 2017;Gallagher et al, 2021;Pujiati, 2019;Suharman, Sejati, & Pratama, 2021). Peningkatan literasi dapat dilakukan melalui diseminasi materi, diskusi, dan tanya jawab.…”
Section: Metodeunclassified
“…Tingkat pemahaman mitra terhadap materi diketahui menggunakan post test. Post test dipilih sebagai media evaluasi karena mampu secara cepat dan valid memvisualisasikan tingkat pemahaman peserta pembelajaran (Suharman et al, 2021). Rincian kegiatan dapat dilihat pada Gambar 2.…”
Section: Metodeunclassified